(untitled) (Research, Society and Development, 2022)
This research presents itself as a study of the integrative bibliographic review type with the main objective of understanding the mechanism of development of shoulder impact syndrome and its possible therapeutic applications, addressing studies on shoulder biomechanics, as well asits bone and muscle components and pointing out new updates through the subject. Shoulder impact syndrome is an inflammatory disease and can present in degenerative forms, has as main effect the mechanical impaction of structures that are located in the subacromial space of the shoulder. It is due to the cumulative effect of many passages of the rotator cuff muscles under the coracoacromial arch, resulting in irritation of the supraspinal tendon, infraspinal, leading to a hypertrophy of the subacromial bursa. Several epidemiological studies indicate that shoulder impact syndrome is the most common disorder of the shoulder girdle, with a high prevalence in individuals aged between 40 and 50 years, not ruling out the hypothesis of occurring in young adults who have sports practices of exhaustion. Based on this assumption, this research becomes a study of high relevance both in the academic environment and for professionals working in the health area. It addresses the therapies used to control inflammation, aiming at the remission of degenerative processes, considering that the anatomy of the patient and the evolutionary phase of the disease are crucial factors for directing the success of treatment, however, new searches to better understand its etiology are crucial.